PERFORMANCE EVALUATION OF A COMBINED ANAEROBIC MEMBRANE BIOREACTOR AND DOWN-FLOW HANGING SPONGE FOR TREATMENT OF SYNTHETIC TEXTILE WASTEWATER: EFFECT OF FLUX AND MICROBIAL COMMUNITY - Istiqomah Arrahmah, Fauziyah
Textile wastewater is known for its danger to aquatic ecosystem due to the chemicals contained in it. Of all chemicals contained, color removal is still a challenge in textile wastewater treatment. The removal of this substance can be effectively done by sequential anaerobic-aerobic treatment. Washout in existing anaerobic technologies become the mayor drawback, and this can be overcame using anaerobic membrane bioreactors (AnMBR). Down-flow hanging sponge (DHS) has proven to be an effective anaerobic post treatment for various wastewater types. However, studies on the usage of combined AnMBR-DHS method for textile wastewater treatment are still inadequate. Therefore, the performance of AnMBR-DHS for textile wastewater treatment is important to evaluate. In this research, synthetic wastewater containing Reactive Black 5 (RB5) azo dye is treated by using a combination of AnMBR with 5 L working volume and third generation DHS with 0.5 L working volume. Inside AnMBR, hollow fiber PVDF with pore size of 0.07 - 0.1 ?m is used. The variations in this research are: AnMBR HRT of 12 and 24 h, DHS HRT of 1.4 and 2.8 h, and membrane fluxes of 2.65 and 5.21 LMH. The microbial community activity in both reactors is analyzed based on the 16s rRNA gene sequence. This research is carried out at NTP condition. The BOD, COD, and color removal reached in this research are 97.3±1.8%, 96.7±0.7%, and 95.2±2.0%, respectively. Most of the removal take place in the AnMBR. Variations of HRT and membrane fluxes do not give significant effect towards the performance of AnMBR-DHS. However, a greater membrane flux and a smaller HRT will increase the rate of membrane surface’s fouling formation. Phylum Proteobacteria dominate the microbial community in DHS, while the AnMBR is dominated by phyla Euryarchaeota, Caldiserica, and Proteobacteria. Some genera in AnMBR were reported for their reducing azo dyes ability, while some in DHS were reported for their ability to degrade sulfonated aromatic amine.